Dental-alveolar Compensatory Phenomena of Malocclusion Class II Angle. Lateral Cephalometric Study - Cristian Romanec; V. Dorobat; G. Zegan (Romanian Society of Oral Rehabilitation, 2011)
The purpose of our study was to identify the dental-alveolar phenomena making up for skeletal imbalances due to malocclusion Class II, using the lateral cephalometry method. The research was carried out on 52 patients (29 girls and 23 boys), aged between 7 and 18 years, chosen from 113 cases clinically diagnosed with malocclusion Class II Angle. The lateral cephalometrie images were processed using the ORTHALIS software, whereas the cephalometric measurements were conducted by means of the Tweed and Steiner method. The databases and statistical analyses were carried out using the SPSS 16.0 software for Windows and descriptive statistics means. The results obtained reveal 5 skeletal patterns of Class II. The dental-alveolar compensation phenomena occurring in the Class II skeletal patterns associated with the skeletal growing patterns identified in the study group took a wide variety of dental-alveolar forms. The wide variety of clinical manifestations and expressions at the skeletal and dental-alveolar levels fully supports the opinion according to which malocclusions Class II Angle are far from being a mere clinical entity, but rather a complex craniodental-maxillo-facial syndrome